If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = 14 + 3(x + 8) Reorder the terms: 24 = 14 + 3(8 + x) 24 = 14 + (8 * 3 + x * 3) 24 = 14 + (24 + 3x) Combine like terms: 14 + 24 = 38 24 = 38 + 3x Solving 24 = 38 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 24 + -3x = 38 + 3x + -3x Combine like terms: 3x + -3x = 0 24 + -3x = 38 + 0 24 + -3x = 38 Add '-24' to each side of the equation. 24 + -24 + -3x = 38 + -24 Combine like terms: 24 + -24 = 0 0 + -3x = 38 + -24 -3x = 38 + -24 Combine like terms: 38 + -24 = 14 -3x = 14 Divide each side by '-3'. x = -4.666666667 Simplifying x = -4.666666667
| 60=2d+d+30 | | 5x+6x+3+8=7x+5+3x | | -0.6*6= | | Y=20sin(3x) | | 2b-4-4b-6= | | 6a-3c= | | 36x-4=4x | | 8-(2+x)=0 | | 59-2x=5-8x | | X^2-3x=-2.25 | | 5x^3+8x^2-2=0 | | 6(a+8)=56 | | 90=5x+3y | | Y=4(x+45)+3x | | 2x-4+90=180 | | 7m=-5m+144 | | 6(t-3)-92=-122 | | -3x-(-2-4x)= | | 6x^4-45x=24x^2 | | 10l=-2l-96 | | 3x-(-2+4x)= | | 15=3x-8x | | 10x=-0.8 | | -4x+5y+3z=-3 | | 5z+7z=12 | | (x^2)-20(x^2-2)+36=0 | | 2k=-3k+105 | | 3x-(2-x)=-1 | | 7x+8y+5z=5 | | -3x+(2-4x)= | | 12h=6h-72 | | 6x+5x=77 |